The Association of Choledochal Cyst and Pancreatitis:A Case Report and Review of the Literature - ÇAĞAN APPAK, YELİZ; GÜNŞAR, CÜNEYT; DOĞAN, GÜZİDE; DOĞAN, GÜZİDE; TARHAN, SERDAR; KASIRGA, HASAN ERHUN (My University, 2017)
Choledochal cysts are relatively rare congenital anomalies which are characterized by dilatation of the extra-and/or intra-hepatic bile ducts. Pancreatic involvement before choledochal cyst operation might be a risk factor for postoperative pancreatitis. In this case report, we present a patient who had pancreatic enzyme elevation before choledochal cyst operation and who developed acute pancreatitis after surgery.